ACCOUNTING PRACTICES IN THE METATAH CEREMONY IN BALINESE COMMUNITY - Fitalia, Ni Ketut Enik; Ridhawati, Rini; Sasanti, Elin Erlina (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to reveal the application of accounting practices in the Metatah ceremony in Balinese community  in Abian Tubuh Baru, Mataram City, West Nusa Tenggara. Research Methods. This research uses a qualitative method with an ethnographic approach through observation, interviews, and documentation with Balinese people as informants. Research Results and Findings. The results show that accounting practices in the Metatah ceremony are based on social values such as gratitude, family ties, mutual cooperation, solidarity, and preservation of Balinese culture. Expenditures in this ceremony are flexible, adjusted to individual abilities and family contributions. The financial recording practices applied are still simple, focusing on recording receipts and expenditures, and are based on the daily habits and experiences of the local community. This research shows that accounting in a cultural context has unique and practical characteristics.